Pharmacokinetics and safety of subcutaneous rituximab plus fludarabine and cyclophosphamide for patients with chronic lymphocytic leukaemia. (29th July 2015) - Assouline, Sarit; Buccheri, Valeria; Delmer, Alain; Gaidano, Gianluca; McIntyre, Christine; Brewster, Michael; Catalani, Olivier; Hourcade‐Potelleret, Florence; Sayyed, Pakeeza; Badoux, Xavier
Abstract : Aims: The aim of the phase Ib, two part SAWYER study (BO25341; NCT01292603) was to investigate the pharmacokinetics and safety of subcutaneous (s.c.) rituximab compared with intravenous (i.v.) rituximab, both in combination with fludarabine and cyclophosphamide (FC), as first line treatment for patients with chronic lymphocytic leukaemia (CLL). Methods: During part 1 (dose‐finding), CLL patients received rituximab i.v. followed by a single dose of rituximab s.c. at one of three fixed doses (1400, 1600 or 1870 mg) in cycle 6. The primary objective was to identify a fixed s.c. dose that would achieve comparable rituximab serum trough concentrations ( C trough ) to those achieved with the standard 4 weekly 500 mg m –2 rituximab i.v. dose. Results: Fifty‐five patients received a fixed dose of rituximab s.c., 16 received 1400 mg, 17 received 1600 mg and 22 received 1870 mg. The 1600 mg dose was predicted to achieve non‐inferior C trough to standard rituximab i.v. treatment. The rituximab s.c. safety profile was comparable with rituximab i.v., except that local administration‐related reactions, mainly mild/moderate injection site reactions, occurred more frequently with rituximab s.c., which was not unexpected. Subcutaneous administration was preferred to i.v. administration by >90% of patients and nurses ( n  = 112). Conclusions: SAWYER part 1 data predict that rituximab s.c. 1600 mg will achieve non‐inferior C trough concentrations to rituximab i.v. 500 mg m –2, administered 4 weekly. This fixed s.c. dose is currently undergoing formal non‐inferiority assessment in SAWYER part 2. In future, CLL treatment regimens comprising rituximab s.c. and oral FC could substantially reduce i.v. chair time.